Comparative Authority in Cybercrime Investigation: Indonesian Police and Related Institutions - John Piter Tampubolon; Rineke Sara (al-Battar: Jurnal Pamungkas Hukum, 2025)
The rapid expansion of information technology has significantly increased cybercrime in Indonesia, necessitating a clear and coordinated law enforcement framework. This article aims to comparatively analyze the authority to investigate cybercrime between the Indonesian National Police (Polri) and other related institutions, including the Attorney General’s Office, the National Cyber and Crypto Agency (BSSN), and the Ministry of Communication and Informatics (Kominfo). The research employs a normative juridical method with statutory and conceptual approaches, supported by comparative analysis of institutional authority based on Law Number 1 of 2024 concerning Electronic Information and Transactions, the Criminal Procedure Code (KUHAP), and Law Number 16 of 2004 concerning the Prosecutor’s Office. The findings indicate that Polri holds dominant and comprehensive investigative authority, while other institutions perform supportive, supervisory, and technical functions without direct investigative attribution. However, regulatory fragmentation and weak coordination mechanisms create overlaps and inefficiencies in cybercrime handling. This study concludes that regulatory harmonization and the establishment of an integrated coordination framework are essential to ensure effective, accountable, and human-rights-oriented cybercrime law enforcement in Indonesia.